Strategies to Increase Online Student Success for Students with Disabilities - Betts, Kristen; Cohen, Alex; Veit, Daniel; Alphin, Henry C.; Broadus, Chanel (Online Learning, 2013)
Online education provides extensive opportunities for individuals with disabilities to enroll in degree and certificate programs. However, accessibility must be a key component of online program development since this can have a profound affect on student engagement in and outside of the online classroom, academic performance, and completion rates. This article provides a unique perspective on accessibility in online education. One current online student and three alumni of online programs provide video self-introductions, an overview of their online experience., and strategies for increasing student success in online courses and programs for students with disabilities. Strategies are also shared for integrating accessibility as a critical component within faculty development to ensure accessibility goes beyond the Office of Disability Services and becomes an integral part of online teaching, learning, and assessment.